The onset of steady marangoni convection in a rotating fluid layer with a prescribed heat flux at its lower boundary / Wartono Sarma, lshak Hashim and Ahmad Kamal Zulkifle - Sarma, Wartono; Hashim, lshak; Zulkifle, Ahmad Kamal (2004)
The effect of uniform rotation on the onset of steady Marangoni convection in a horizontal fluid layer heated from below is considered theoretically. The fluid layer is bounded below by a rigid plane boundary with a prescribed heat flux and above by a free non-deformable surface subject to a uniform vertical temperature gradient. The theoretical analysis follows the usual small-disturbance approach of perturbation theory and leads, at the marginal state, to a functional relation between the Marangoni and Taylor numbers which is then computed numerically.